Cover Image. Issue 1 (20th December 2017) - Sato, H.; Takahashi, K.; Nakajima, N.; Hasegawa, G.; Mizuno, K.; Hashimoto, S.; Ikarashi, S.; Hayashi, K.; Honda, Y.; Yokoyama, J.; Sato, Y.; Terai, S.
Abstract : The cover image, by H. Sato et al., is based on the Original Article Full-layer mucosal histology in achalasia: Histological epithelial wave is characteristic in "pinstripe pattern"-positive achalasia, DOI:10.1111/nmo.13168 .